Uncovering facts and values : studies in contemporary epistemology and political philosophy - Kuzniar, Adrian. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2016)
This volume addresses issues in epistemology, ethics and political philosophy. It contains new papers on issues such as semantic theory of truth, sandwich theory of knowledge, American pragmatism and scepticism, arguments from ignorance, infallibilism and fallibilism, justification and confirmation, Tarski's T-schema, experimental results and ordinary truth, epistemic comparativism and experiments, epiphenomenlism and eliminativism about the mental, the identity theory of truth, thoughts and facts, metaontological maximalism and minimalism, morality and rights, aggregation of value judgements and aggregation of preferences, conditional and unconditional ethics, the role of the theory of evolution in moral epistemology, global and international political community, Rawls' views on cosmopolitanism and global justice, international distributive justice. Contributors are: Tomasz Bigaj, Krzysztof Brzechczyn, Tadeusz Buksiński, Robin Cameron, Jan B. Deręgowski, Nigel Dower, Adam Grobler, Jesper Kallestrup, Adrian Kuźniar, Justyna Miklaszewska, Joanna Miksa, Joanna Odrowąż-Sypniewska, Katarzyna Paprzycka, Krzysztof Posłajko, Wlodek Rabinowicz, John Skorupski, Leslie Stevenson, Piotr Szałek, Tadeusz Szubka, Joseph Ulatowski, Jan Woleński, Rafał Wonicki, Anna Wójtowicz, Renata Ziemińska